Long-term optical monitoring of η Carinae: Multiband light curves for a complete orbital period - Fernández Lajús, Eduardo (2009)
Context. The periodicity of 5.5 years for some observational events occurring in η Carinae manifests itself across a large wavelength range and has been associated with its binary nature. These events are supposed to occur when the binary components are close to periastron. To detect the previous periastron passage of η Car in 2003, we started an intensive, ground-based, optical, photometric observing campaign. Aims. We continued observing the object to monitor its photometric behavior and variability across the entire orbital cycle. Methods. Our observation program consisted of daily differential photometry from CCD images, which were acquired using a 0.8 m telescope and a standard BVRI filter set at La Plata Observatory. The photometry includes the central object and the surrounding Homunculus nebula. Results. We present up-to-date results of our observing program, including homogeneous photometric data collected between 2003 and 2008. Our observations demonstrated that η Car has continued increasing in brightness at a constant rate since 1998. In 2006, it reached its brightest magnitude (V - 4.7) since about 1860. The object then suddenly reverted its brightening trend, fading to V = 5.0 at the beginning of 2007, and has maintained a quite steady state since then. We continue the photometric monitoring of η Car in anticipation of the next "periastron passage", predicted to occur at the beginning of 2009.